Efektivitas Mindfulness dalam Meningkatkan Resiliensi Akademik Siswa Abab 21: Kajian Literatur Terkini - Sandra, Rober; F, Firman; N, Netrawati (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The 21st century presents various complex challenges for students, including academic pressure, technological demands, and rapid social changes. In this context, the ability to have academic resilience becomes very important for students to be able to survive and thrive. This literature review aims to analyze the role of mindfulness practice in enhancing students' academic resilience. Mindfulness, which is the practice of full awareness of the present moment without judgment, has been identified as an intervention that has the potential to strengthen students' mental resilience. Various studies show that mindfulness practice can enhance emotional regulation, impulse control, and self-efficacy in students, all of which are important components of academic resilience. Additionally, programs like Mindfulness-Based Stress Reduction (MBSR) have proven effective in reducing academic stress and enhancing student well-being. However, the implementation of mindfulness in the educational context still faces various challenges, including the lack of training for educators and limited resources. Therefore, collaboration between educators, policymakers, and researchers is needed to effectively integrate mindfulness practices into the educational curriculum to support students' academic resilience in the modern era.